2017
DOI: 10.1111/jedm.12141
|View full text |Cite
|
Sign up to set email alerts
|

A New Statistic for Detection of Aberrant Answer Changes

Abstract: As noted by Fremer and Olson, analysis of answer changes is often used to investigate testing irregularities because the analysis is readily performed and has proven its value in practice. Researchers such as Belov, Sinharay and Johnson, van der Linden and Jeon, van der Linden and Lewis, and Wollack, Cohen, and Eckerly have suggested several statistics for detection of aberrant answer changes. This article suggests a new statistic that is based on the likelihood ratio test. An advantage of the new statistic is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The use of ΛST was found, in our simulations, to lead to low power and inadvertent flagging of those who performed worse or slower on the compromised items, and is not considered further. Also, Sinharay, Duong, and Wood (2017) emphasized the need to use one‐sided hypothesis testing in detection of test fraud.…”
Section: Method: a New Statistic Based On Item Scores And Response Timesmentioning
confidence: 99%
“…The use of ΛST was found, in our simulations, to lead to low power and inadvertent flagging of those who performed worse or slower on the compromised items, and is not considered further. Also, Sinharay, Duong, and Wood (2017) emphasized the need to use one‐sided hypothesis testing in detection of test fraud.…”
Section: Method: a New Statistic Based On Item Scores And Response Timesmentioning
confidence: 99%
“…Erasure analysis was also performed at the individual level using the L-index (Sinharay, Duong, & Wood, 2017). The values of the L-index agree with the values of EDI g , EDI g N , and EDI g A for the data set.…”
Section: Resultsmentioning
confidence: 99%
“…There are several limitations of this article and, consequently, several related topics can be further investigated. First, it is possible to extend other indices for detection of fraudulent erasures for individual examinees including those suggested by Sinharay and Johnson (2017), Sinharay et al (2017), and van der Linden and Lewis (2015) to the group level and a future study may compare the extensions suggested in this article to extensions of other individual-level statistics for detecting fraudulent erasures. Second, while our simulation study was detailed, it is possible to perform more simulations, possibly with other IRT models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations